2013
DOI: 10.1016/j.bbadis.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of kinase PKC-zeta in the p62/p62P392L-driven activation of NF-κB in human osteoclasts

Abstract: Mutations of the gene encoding sequestosome1 (SQSTM1/p62), clustering in or near the UBA domain, have been described in Paget's disease of bone (PDB); among these the P392L substitution is the most prevalent. Protein p62 mediates several cell functions, including the control of NF-κB signaling, and autophagy. This scaffolding protein interacts with atypical PKCζ in the RANKL-induced signaling complex. We have previously shown that osteoclasts (OCs) overexpressing the p62(P392L) variant were in a constitutively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…To evaluate the expression of the encoded proteins, we used OCs derived from cord blood monocytes (CBMs), and investigated the protein-level expression by immunofluorescence and western blot using specific antibodies. Our objective was to confirm the expression of the proteins encoded by the selected genes in human OCs, for which the CBM-derived OCs represent a reliable model [8],[14],[22]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the expression of the encoded proteins, we used OCs derived from cord blood monocytes (CBMs), and investigated the protein-level expression by immunofluorescence and western blot using specific antibodies. Our objective was to confirm the expression of the proteins encoded by the selected genes in human OCs, for which the CBM-derived OCs represent a reliable model [8],[14],[22]. …”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the SQSTM1 gene have been identified in a high proportion of PDB patients [6], the p62P392L substitution being the most frequent [7]. In PDB, p62P392L contributes at least in part to the induction of an activated stage in OCs by stimulating signaling pathways that can lead to NF-κB activation [5],[8]. In vivo , knock-in mice expressing p62 P394L (the murine equivalent of human p62 P392L ) develop focal osteolytic lesions, some of which resemble PDB lesions [9], although in another study, co-expression of the measles virus nucleocapsid gene in the OC lineage was required [4].…”
Section: Introductionmentioning
confidence: 99%
“…5). PKCζ, besides binding with munc18c leading to the Glut 4 vesicle fusion to the plasma membrane [25], has also been demonstrated to interact with p62 in different cell lines and tissues [9,17,26,48]. Therefore, the binding between PKCζ and p62 might affect the interaction between PKCζ and munc18c.…”
Section: Unacylated Ghrelin Restored Impaired Insulin Signaling In DImentioning
confidence: 95%
“…It has been suggested that p62 forms a complex with TRAF-6 and aPKC, which is critical for RANKL-induced NF-κB activation 6, 42, 43 . Mutations in the UBA domain results in loss of UBA function and also activate TRAF6–NF-kB signaling, which results in increased osteoclastogenesis 8, 39, 44 . p62 KO mice also show a similar phenotype reminiscent of Paget’s disease with impaired NF-κB activation 6 , further supporting that p62 is an important mediator regulating bone homeostasis.…”
Section: Structure and Multiple Functions Of P62mentioning
confidence: 99%